Analysis and Characterization of Bioethanol from Banana (Musa Acuminata Balbisiana) Peel Pulp by Yeast Enzymatic Production - Khusna Widhyahrini; Endah Nur Hidayat (Jurnal Kartika Kimia, 2019)
Banana (Musa acuminata balbisiana) peel had some potential using, especially in bioethanol. It was indicated that Banana peel (Musa acuminata balbisiana) had carbohydrates abundance. Banana (Musa acuminata balbisiana) peel can be cropped in some season, not only in a specific seasons. So that, Banana (Musa acuminata balbisiana) peel could be gotten easily. Banana (Musa acuminata balbisiana) peel as the trash is usually thrown away or animal feed needed. Banana (Musa acuminata balbisiana) peel had carbohydrate higher content, so it gave a lot of potential in bioethanol application. But, we needed to understand about the results of fermentation process. Characterization had been done to understand the fermentation of Banana peel product. The raw materials gotten from dried Banana peel with the amount of 50 gram in each of 100 ml beaker glass. The yeast solution had been made in 15% (w/v), 25% (w/v), and 35% (w/v) in water solvent. The fermentation process was carried out during 96 hours, then the clear liquid was separated by decantation process from the mixture. The distillation process was done to purify the product on 80°C degrees. The distillate was measured by Fourier Transform Infrared (FTIR) spectroscopy to identify the specific peaks. The FTIR measurement was used Octagonal Cell Windows FTIR Prestige 21 Shimadzu. The FTIR spectrum showed characteristic peaks of bioethanol at 3404.01 cm-1 (-OH bonds); 2933.54 cm-1 (-C-H bonds); and 1011.06 cm-1 (-C-O bonds). From the FTIR analysis could be concluded that fermentation of Banana peel gave bioethanol. Keywords: Bioethanol, Banana peel, yeast, fermentation process, Biocatalyst